Facilitation or hindrance? The impact of downward social comparison on adversarial growth - Nie, Ting; Wu, Jing; Yan, Qiao (Frontiers in Psychology, 2024)
Introduction While adversity can bring great challenges to individuals' life and work, many people also find ways to make positive changes and adapt to these difficult circumstances. Individuals tend to make social comparisons more frequently and intensely when faced with adversity or high stress. The study attempts to examine the influence mechanism of downward social comparison on individual adversarial growth. Methods By collecting data from 353 Chinese who have experienced adversities in the past 3 years, the study validates the dual mediating model of gratitude and self-acceptance and explores the moderating effect of interpersonal sensitivity. Results The findings indicate that: downward social comparison can increase the occurrence of adversarial growth by enhancing individuals' self-acceptance and gratitude. Compared to individuals with low interpersonal sensitivity, individuals with high interpersonal sensitivity are more likely to facilitate the occurrence of adversarial growth through self-acceptance and gratitude due to downward social comparison. Discussion In the face of adversity, individuals can regain self-confidence and respond positively by comparing themselves to people in worse situations than themselves. In particular, individuals with higher interpersonal sensitivity are more likely to benefit from downward social comparisons and grow from adversity.